PERENCANAAN STRUKTUR KANTOR PHICOS DENGAN SISTIM RANGKA BAJA PEMIKUL MOMEN KHUSUS - Rasyiid Lathiif Amhudo (Jurnal Teknik Sipil dan Arsitektur, 2024)
Colomadu is the name of a district in Karanganyar Regency, Central Java. Colomadu's economic growth can grow through the goods and services business, tourism, and industry so that an office building is planned in the Colomadu area. Because the location of Colomadu District is not far from the province of Yogyakarta, where earthquakes often occur, an earthquake-resistant building is needed to anticipate a minimum number of casualties and material losses during an earthquake. Therefore, in planning this office, a special moment resisting frame system (SRPMK) is used. The building with the Special Moment Bearing Frame System (SRPMK) is planned with the concept of Strong Column and Weak Beam (strong column and weak beam). This planning aims to plan a building structure that is resistant to earthquake loads that will be received by the structure using a special moment-bearing frame structure system and refers to the applicable requirements in accordance with SNI 2847: 2019. Earthquake loads are reviewed using the spectrum response method and structural analysis is carried out with the help of the ETABS V9.7.4 program. From the planning results, the dimensions of the bondek floor plate thickness of 140 mm, beams B1A 150x400 mm, B2A 200x400 mm, B2B 200x400 mm, B2C 200x400 mm, B2D 200x400 mm, B2E 200x400 mm, B3A 200x500 mm, B3B 200x500 mm, B4A 300x150 mm, B5A 300x150 mm, BS 150x300 mm, and columns KP 150x150 mm, K1A 200x300 mm, K2A 400x550 mm, K3A 450x650 mm, and K4A 350x500 mm.